Exploring Gen-Z's Self-Efficacy and Perceived Urgency of English Proficiency for International Program - Abdurrohman Septiadi; Riskayadi (CV. Mitkom Indotama, 2026)
This transcendental phenomenological study examines how Generation Z university students in Bangka Belitung, a peripheral Indonesian province, experience English self-efficacy and perceive the urgency of developing proficiency for international mobility programs. While literature often focuses on metropolitan hubs, this study addresses the empirical gap in under-resourced regions by examining self-efficacy and urgency as an interacting pair. Semi-structured interviews were conducted with 12 purposively sampled students, and data were analyzed via Colaizzi’s method. Four themes emerged: English as a